2000
DOI: 10.1159/000057504
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay for Renewable Energy: Implications for UK Green Tariff Offerings

Abstract: Although financial support for renewable electricity sources has existed via the non-fossil fuel obligation since 1990, the UK ‘green power’ market is still in its infancy. This paper looks at attitudes to tariffs for ‘green power’ in light of the proposed phase-out of the non-fossil fuel obligation. The hypothesis tested was the consumers’ willingness to pay for electricity generated from renewable energy sources and to see if this was related to income and attitude. Data for analysis were taken from replies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…This goes the same with the years of survey with the exception of [45,76]who carried out their survey in 1999 and 1996. The publication and survey years indicate that interest and awareness on RES are on the rise in the recent decade.…”
Section: Descriptive Statisticssupporting
confidence: 63%
See 1 more Smart Citation
“…This goes the same with the years of survey with the exception of [45,76]who carried out their survey in 1999 and 1996. The publication and survey years indicate that interest and awareness on RES are on the rise in the recent decade.…”
Section: Descriptive Statisticssupporting
confidence: 63%
“…There are however, three studies that provide WTP in percentages but with sufficient information for us to compute the mean WTP and its corresponding variance. We therefore include these studies into our analysis [44][45][46].…”
Section: Excluded Studiesmentioning
confidence: 99%
“…Bigerna and Polinori [23] and Abdullah and Jeanty [24] ,5 reached similar findings as well with respect to income, age, and education for Italy and Kenya, respectively. Sardianou and Genoudi [25] found 'age' and 'education' to be statistically significant factors in Greece influencing the adoption of RE, in contrast to Diaz-Rainey and Ashton [26] who found these variables to be statistically insignificant in the U.K. Batley et al [12] also indicated that WTP extra for RE is sensitive to income.…”
Section: Literature Reviewmentioning
confidence: 95%
“…WTP studies can either estimate the influence of various independent variables on the dichotomous decision to pay (or not to pay) for renewable electricity (for example, see [11][12][13][14]), and/or estimate the percentage premiums or absolute amounts that individuals are willing to pay (e.g. [16]).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation